Analisis Keandalan Transformator Daya Menggunakan Metode Distribusi Weibull Di Gardu Induk Garuda Sakti Pekanbaru - Suryadi, Suryadi; Firdaus, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
To provide a reliable service, the power system must remain intact and able to cope with various problems that may occur. In this study discussed on Power Transformer Reliability Analysis Method Using Weibull distribution based on the value of the MTTF. Weibull statistics have been widely used as a mathematical method for calculating failure rate, reliability, and predict the remaining life time of equipment. From the calculation, the parameter value is 1.8402 shape and scale parameter value is 1.1711. MTTF value of 0.3597 years, the uptime value of 2.6402 years, reliability value of 0.8800.Keywords: Reliability, Distribution Weibull.